2006
DOI: 10.1016/j.bbadis.2006.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The lack of effect of glucosamine sulphate on aggrecan mRNA expression and 35S-sulphate incorporation in bovine primary chondrocytes

Abstract: Glucosamine and glucosamine sulphate have been promoted as a disease-modifying agent to improve the clinical symptoms of osteoarthritis. The precise mechanism of the action of the suggested positive effect of glucosamine or glucosamine sulphate on cartilage proteoglycans is not known, since the level of glucosamine in plasma remains very low after oral administration of glucosamine sulphate. We examined whether exogenous hexosamines or their sulphated forms would increase steady-state levels of aggrecan and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…On the other hand, studies with human and MC615 mouse chondrocytes have indicated that glucosamine does not stimulate CS synthesis, and a high concentration of glucosamine even inhibits CS synthesis Silbert 2003, 2004). In our previous studies (Qu et al 2006(Qu et al , 2007, we have been unable to see any positive effect of GS on ECM production or gene expression even at 1 mM concentrations. Since the supplementation period (10 days) was relatively short compared with the recommended minimum used time for GS, we decided to test whether a remarkably longer exposure to GS would show beneficial effects.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…On the other hand, studies with human and MC615 mouse chondrocytes have indicated that glucosamine does not stimulate CS synthesis, and a high concentration of glucosamine even inhibits CS synthesis Silbert 2003, 2004). In our previous studies (Qu et al 2006(Qu et al , 2007, we have been unable to see any positive effect of GS on ECM production or gene expression even at 1 mM concentrations. Since the supplementation period (10 days) was relatively short compared with the recommended minimum used time for GS, we decided to test whether a remarkably longer exposure to GS would show beneficial effects.…”
Section: Discussionmentioning
confidence: 81%
“…Preparation of chondrocyte-seeded culture inserts Isolated primary chondrocytes were obtained from the articular cartilage of bovine (estimated age: 13-22 months) femoral condyles by collagenase (Sigma-Aldrich, St. Louis, Mo., USA) digestion (Qu et al 2006). Subsequently, the isolated chondrocytes were washed twice with PBS, counted, and plated at cell density of 6×10 6 chondrocytes per transwell-COL insert, which was located inside a 24-well plate.…”
Section: Equilibrium Of Inserts Before Cell Seedingmentioning
confidence: 99%
“…Therefore, a question has been raised whether such a low concentration can increase cartilage PG synthesis, as has been suggested for OA chondrocytes (Bassleer et al 1998;Dodge and Jimenez 2003). Previously, we have been unable to confirm that exogenous GS in low-or highglucose DMEM increases aggrecan mRNA expression or GAG synthesis (Qu et al 2006(Qu et al , 2007a.…”
Section: Discussionmentioning
confidence: 94%
“…[ 35 S]-sulphate (5 µCi/ml) was added into each well of the 12-well plates and then the cultures were incubated in humidified 5% or 20% O 2 incubators at 37°C with 5% CO 2 for 24 h. The supernatants were collected and the amounts of incorporated and free [ 35 S]-sulphate were analysed as in our previous study (Qu et al 2006). The volumes used for the analysis were so adjusted that a good separation between the GAG incorporated and the free unincorporated label could be achieved.…”
Section: [ 35 S]-sulphate Incorporation Analysismentioning
confidence: 99%
See 1 more Smart Citation